Evaluating the information architecture (IA) of Agribazaar 2.0 web-based system using web architectural inducing model (WAIM) framework / Noor Syazana Md. Yusof - Md. Yusof, Noor Syazana (2013)
The art and science of website's organizing and labeling, intranets, communities in online application, and usability that supported by software is all about the information architecture. As information proliferates rapidly fast usability became a critical success factor for websites and software applications. Well value of IA is a foundation needed for an information system that made sense to the user. Evaluating the Information Architecture of Agribazaar 2.0 Web-Based System is to revealed issues pertaining to the Information Architecture (IA) aspects of the AgriBazaar Web-Based System and evaluates the Web-based System in terms of Information Architecture. The preliminary investigation was done through the interview and observation with an expert of Human Computer Interaction. However, the evidences revealed IA issues based on the preliminary investigations. Therefore, an experimental study should be conducted to evaluate the system based on the IA aspects. AgriBazaar 2.0 Web-Based System was developed since 2008 and being deployed in the Web-Based System in 2011. However, this system has not yet been evaluated in terms of Information Architecture. Thus, there is a need to evaluate the IA of Agribazaar 2.0 Web-Based Systems and investigate its usability through the experimental study intended for design the new prototype of IA.